Olfactory sensitivity to changes in environmental [Ca2+] in the marine teleost Sparus aurata - Hubbard, Peter (2014)
Estuarine and/or migratory teleosts may experience large and rapid changes in external [Ca2+]. Previous studies have largely centred on the physiological mechanisms that maintain a constant plasma [Ca2+] in the face of such external fluctuations, but little work has been directed to examining how these changes may originally be detected. We present evidence that the olfactory system of the gilthead seabream (Sparus aurata) is highly sensitive to reductions in environmental [Ca2+] and suggest a possible mechanism by which this may be mediated. Multi-unit extracellular recordings were made from the olfactory nerve of Sparus aurata while the [Ca2+] of artificial sea water flowing over the olfactory epithelium was varied from 10 to 0mmoll-1. Reductions in [Ca2+] caused a large, nonaccommodating increase in the firing rate of the olfactory nerve (apparent IC50=1.67±0.26mmoll-1, apparent Hill coefficient=-1.22±0.14; means ± S.E.M., N=6). This response was not due to the concomitant reduction in osmolality and was specific for Ca2+. During continuous exposure of the olfactory epithelium to Ca2+-free sea water, the apparent IC50 and Hill coefficient in response to increases in [Ca2+] were 0.48±0.14mmoll-1 and -0.76±0.16 (means ± S.E.M., N=6), respectively, suggesting an adaptation of the Ca2+- sensing system to low-[Ca2+] environments. Ca2+ is intimately involved in signal transduction in the olfactory receptor neurones, but our data support a true olfactory response, rather than a non-specific effect to lowering of external [Ca2+]. The absence of Ca2+ from sea water only partially and temporarily blunted the olfactory response to the odorant L-serine; the response amplitude recovered to control levels within 20 min. This suggests that the olfactory system in general is able to adapt to low-[Ca2+] environments. We suggest that the Ca2+ sensitivity is mediated by an extracellular Ca2+-sensing receptor similar to the recently characterized mammalian Ca2+-sensing receptor.